2022
DOI: 10.1002/evl3.308
|View full text |Cite
|
Sign up to set email alerts
|

The genomic scale of fluctuating selection in a natural plant population

Abstract: This study characterizes evolution at ≈1.86 million Single Nucleotide Polymorphisms (SNPs) within a natural population of yellow monkeyflower (Mimulus guttatus). Most SNPs exhibit minimal change over a span of 23 generations (less than 1% per year), consistent with neutral evolution in a large population. However, several thousand SNPs display strong fluctuations in frequency. Multiple lines of evidence indicate that these ‘Fluctuating SNPs’ are driven by temporally varying selection. Unlinked loci exhibit syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…Similarly, there is no cancelling out across generations, e.g. seasonally fluctuating selection must incur many selective deaths in order to effect the large allele frequency fluctuations that have been observed around the long-term mean (Kelly 2022; Machado et al 2021; Rudman et al 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there is no cancelling out across generations, e.g. seasonally fluctuating selection must incur many selective deaths in order to effect the large allele frequency fluctuations that have been observed around the long-term mean (Kelly 2022; Machado et al 2021; Rudman et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, there is no cancelling out across generations, e.g. seasonally fluctuating selection must incur many selective deaths in order to effect the large allele frequency fluctuations that have been observed around the long-term mean (Kelly 2022; Machado et al 2021; Rudman et al 2022). This high demand for selective deaths also applies, given life history trade-offs, to unobserved effects that more quickly cancel out between successive life history transitions.…”
Section: Resultsmentioning
confidence: 99%
“…This species exhibits remarkably high gene sequence and insertion/deletion (indel) variation, even within local populations [30]. In fact, it is difficult to reliably map Illumina sequencing reads to intergenic regions of the M. guttatus reference genome where indel variation is very high [31]. Such variation could affect gene expression insofar as binding of regulatory elements to the DNA surrounding genes affects expression.…”
Section: Discussionmentioning
confidence: 99%
“…Many different modes of selection are expected to generate these covariance patterns (Buffalo & Coop, 2020; Santiago & Caballero, 1998). This approach has been applied to experimental evolution datasets (Brennan et al, 2022; Buffalo & Coop, 2020) and to natural populations where temporal sampling is available (in Mimulus , oaks and cod; Kelly, 2022; Reid et al, 2023; Saleh et al, 2022). These applications, along with related methods (Bertram, 2021), have revealed that a reasonable proportion of total allele frequency change, especially in artificial selection experiments, can be attributed to widespread selection beyond just a few outliers.…”
Section: Introductionmentioning
confidence: 99%